Evaluation of neuroprotection by melatonin against adverse effects of prenatal exposure to a nonsteroidal anti-inflammatory drug during peripheral nerve development. Issue 41 (April 2015) - Keskin, Ilknur; Kaplan, Suleyman; Kalkan, Serpil; Sutcu, Mustafa; Ulkay, M. Basak; Esener, O. Burak
Highlights: Drugs used in the present study included diclofenac sodium and melatonin. Prenatal diclofenac sodium administration reduces the number and diameter of axons but not myelin sheet in the sciatic nerve. Melatonin can eliminate harmful effects of diclofenac sodium. Abstract: The potential ability of melatonin to protect against impairment of the fetal peripheral nerve system due to maternal consumption of diclofenac sodium (DS) was investigated. Eighty-four pregnant rats were divided into seven groups: control (CONT), saline administered (PS), DS administered (DS), DS with low-dose melatonin administered (DS + MLT10), DS with high-dose melatonin administered (DS + MLT50), low-dose melatonin administered (MLT10), and high-dose melatonin administered (MLT50). After the pregnancy, six male newborn rats from each group were sacrificed at 4 and 20 weeks of age. Their right sciatic nerves were harvested, and nerve fibers were evaluated using stereological techniques. Mean numbers of myelinated axons, axon cross-section areas and the mean thickness of the myelin sheet were estimated. Four-week-old prenatally DS-exposed rats had significantly fewer axons, a smaller myelinated axonal area, and a thinner myelin sheath compared to CONT group ( p < 0.05). Although melatonin at both doses significantly increased axon numbers, only a high dose of melatonin increased the diameter of those axons ( p < 0.05). At 20-weeks of age, myelinated axon number in the DS group was not only significantly lower than all other groups ( p < 0.05) but also the cross-sectional area of these axons was smaller than all other groups ( p < 0.05). There were no differences between the groups regarding the mean thickness of the myelin sheet. The current study indicates that prenatal exposure to DS decreases the number and the diameter of sciatic nerve axons and that melatonin prophylaxis can prevent these effects.